Diklat Strategi Pembelajaran Berbasis Literasi dalam Upaya Peningkatan Kualitas Pendidikan Bagi Guru Bahasa Jepang - Cahyono, Agus; Saragih, Febi Ariani; Hadinata, Vanda (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to provide education and training in learning strategies that are useful for the teaching and learning process in accordance with government requirements. This is based on the observation that most teachers in Indonesia do not receive continuous professional development, and only a few teachers receive guidance from external facilitators, school principals, supervisors, or experienced fellow teachers. The low quality of teachers is one of the causes of the low quality of education. Fundamental changes are needed in the education system, especially those that focus on improving teacher competence, in order to create a quality learning process. One way to achieve this is by organizing training for teachers, especially Japanese language teachers in the Malang Raya area, who rarely have the opportunity to improve their competence. The learning method currently being promoted by the government is the 21st-century learning method. However, to date, many teachers still conduct teaching and learning processes that are not based on 21st-century thinking processes, which require the implementation of critical, collaborative, communicative, and creative thinking. The implementation of 21st-century learning processes does indeed require specific knowledge and effort, making teachers reluctant to implement them. Training in literacy-based learning strategies is one effort to overcome this problem.